STRATEGI DAN TAHAPAN MANAJEMEN KRISIS DALAM KAJIAN PUBLIC RELATIONS: SEBUAH TINJAUAN DALAM PERSPEKTIF ISLAM - Rohayati Rohayati (An-Nida', 2018)
Crisis is a problem for every organizations. Crisis can suddenly occur without knowing the time and place, an appropriate planning is needed to facing the crisis. Facing the crisis is one of the roles of Public Relations, which is very important to pay attention to the right stages in handling it. Public Relations is a vital of the companies. The fate of companies is very dependent on how the Public Relations handling the crisis. The role of the PR is determinant of the success or failure of the companies to go throught a crisis while at the same time carrying out recovery steps. A Proper crisis management will maintain the sustainability of the companies.